1999
DOI: 10.1159/000010059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Add-Back Therapy on Bone Mineral Density and Pyridinium Crosslinks in Patients with Endometriosis Treated with Gonadotropin-Releasing Hormone Agonists

Abstract: Treatment of endometriosis with gonadotropin-releasing hormone agonists (GnRHa) is limited to 6 months because of possible adverse effects on bone metabolism. We designed a randomized, double-blind, placebo-controlled, prospective study of 27 patients with endometriosis who were given GnRHa with or without hormone add-back therapy (+ 20 µg of ethinyl estradiol with 0.15 mg desogestrel) designed to suppress the adverse effects of hypoestrogenism while preserving the efficacy of GnRHa. Both regimens showed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is generally not considered appropriate to treat with a GnRHa alone because of a substantial reduction in bone mineral density (BMD), significant symptoms of estrogen deficiency such as hot flashes [ 11 , 12 ], and sexual complaints such as the loss of libido and vaginal dryness. The use of add-back sex steroids with GnRH analogues is aimed at preventing the negative effects of the GnRHa while maintaining an effective therapy for endometriosis [ 13 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally not considered appropriate to treat with a GnRHa alone because of a substantial reduction in bone mineral density (BMD), significant symptoms of estrogen deficiency such as hot flashes [ 11 , 12 ], and sexual complaints such as the loss of libido and vaginal dryness. The use of add-back sex steroids with GnRH analogues is aimed at preventing the negative effects of the GnRHa while maintaining an effective therapy for endometriosis [ 13 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contradicting this result Moghissi et al (5) and others have shown a positive effect on BMD by hormone replacement therapy (HRT). However, add‐back therapy with estrogen reduces the positive effect of GnRH analog therapy on endometriosis (6). Parathyroid hormone prevents bone loss in women with endometriosis treated with GnRH analogs (7), whereas nasal administration of calcitonin is ineffective (8).…”
mentioning
confidence: 99%